Does International Law Acknowledge Restorative Justice? - Sulbadana Sulbadana; Haniyatul Husna binti Md Mohtar; Andi Intan Purnamasari; Supriyadi Supriyadi (Faculty of Law, Sriwijaya University, Indonesia, 2023)
Global criminal political considerations are strengthening national laws to realise Restorative Justice for the achievement of recovery for victims, perpetrators and the social order of society. The perspective of Restorative Justice can not only be seen from the concept of national law but of course, it can also be seen from the perspective of International Law. One form of Restorative Justice includes Diversi in the Juvenile Criminal Justice System, where Diversi is the result of International Conventions, one of which is the United Nations Rules for The Protection of Juvenile Deprived of Their Liberty (UNRPJ). This paper focuses on the principle that the purpose of criminalising and rectifying criminals is not only a national problem by a particular state but also a general problem by all countries. The research uses a Normative Juridical method with a statute approach, concept and doctrine approach. This research specifically how the contribution of international law in strengthening the ideas and values of Restorative Justice, and its conclusion, restorative justice in the development of criminal policy needs to be given a special space, namely given space for the implementation of restorative justice through policy modify which of course puts forward the idea of recovery for victims, perpetrators and also the community. Restorative justice is familiar in international law, even via the UN congress greater than as soon as it has issued thoughts of struggle by promoting restorative justice. An extra humanist purpose is to be the primary character of international law, as is the precept of worldwide law that each conflict that arises requires a decision that has to be primarily based on humanity.